New Positive Ca(2+)-Activated K(+) Channel Gating Modulators with Selectivity for K(Ca)3.1 - Coleman, Nichole (The American Society for Pharmacology and Experimental Therapeutics, 2014)
Small-conductance (K(Ca)2) and intermediate-conductance (K(Ca)3.1) calcium-activated K(+) channels are voltage-independent and share a common calcium/calmodulin-mediated gating mechanism. Existing positive gating modulators like EBIO, NS309, or SKA-31 activate both K(Ca)2 and K(Ca)3.1 channels with similar potency or, as in the case of CyPPA and NS13001, selectively activate K(Ca)2.2 and K(Ca)2.3 channels. We performed a structure-activity relationship (SAR) study with the aim of optimizing the benzothiazole pharmacophore of SKA-31 toward K(Ca)3.1 selectivity. We identified SKA-111 (5-methylnaphtho[1,2-d]thiazol-2-amine), which displays 123-fold selectivity for K(Ca)3.1 (EC(50) 111 ± 27 nM) over K(Ca)2.3 (EC(50) 13.7 ± 6.9 μM), and SKA-121 (5-methylnaphtho[2,1-d]oxazol-2-amine), which displays 41-fold selectivity for K(Ca)3.1 (EC(50) 109 nM ± 14 nM) over K(Ca)2.3 (EC(50) 4.4 ± 1.6 μM). Both compounds are 200- to 400-fold selective over representative K(V) (K(V)1.3, K(V)2.1, K(V)3.1, and K(V)11.1), Na(V) (Na(V)1.2, Na(V)1.4, Na(V)1.5, and Na(V)1.7), as well as Ca(V)1.2 channels. SKA-121 is a typical positive-gating modulator and shifts the calcium-concentration response curve of K(Ca)3.1 to the left. In blood pressure telemetry experiments, SKA-121 (100 mg/kg i.p.) significantly lowered mean arterial blood pressure in normotensive and hypertensive wild-type but not in KCa3.1(−/−) mice. SKA-111, which was found in pharmacokinetic experiments to have a much longer half-life and to be much more brain penetrant than SKA-121, not only lowered blood pressure but also drastically reduced heart rate, presumably through cardiac and neuronal K(Ca)2 activation when dosed at 100 mg/kg. In conclusion, with SKA-121, we generated a K(Ca)3.1-specific positive gating modulator suitable for further exploring the therapeutical potential of K(Ca)3.1 activation.